Pengaruh Jus Tomat Segar (Lycopersicon esculentum Mill) terhadapKadar Trigliserida dalam Darah Tikus Wistar Jantan yang Diberi Lipid Peroral (The Effect of Fresh Tomato Juice (Lycopersicon esculentum Mill) to The Triglyceride Levels in The Blood of Male W - Riclas Yusuf Punta Wibisono; Happy Harmono; Erna Sulistyani (Pustaka Kesehatan, 2014)
Increased levels of lipid which is characterized by increasedlevels of triglycerides until now has not found an effective and efficient. Some sources say there are9-oxo-ODA in tomatoes to cause triglyceride levels in the blood. Purpose : The aim of The Study todetermineeffect of tomatoe juice on blood serum Triglycerides level inmalewistarrat. This experimental study used male wistar rats, and the post test only control group design. Rats were divided into three groups, i.e. negative control group (K-), positif control group (K+), and treatment group (P). K-group was untreated by fresh tomato juice and fed with standart diet only. K+ group was fed with standart and peroral lipid. P group treated with fresh tomato juice and also fed with standart and lipid peroral.Fresh Tomato juice were treated by means of stomach sondation for 14 days. On day the 15th, rats were sacrified and intracardial blood were taken 3-5 ml for examination of lipid profile by enzimatic colorimetric method using an automatic test analizer. Data were analyzed by one way anova followed by LSD test. The conclusion of this study is the average triglyceride levels between the negative control group (K-) and positive control (K +) was not significantly different, and no changes in triglyceride levels in the control group (K +) and the treatmentgroup. Keywords: tomato juice, Triglycerides, 9-oxo-ODA